Radiation combined with temozolomide contraindicated for young adults diagnosed with anaplastic glioma - Yang, Pei (Oncotarget, 2016)
PURPOSE: Age is a major prognostic factor for malignant gliomas. However, few studies have investigated the management of gliomas in young adults. We determined the role of survival and treatment in young adults with advanced gliomas in a large population from the Chinese Glioma Genome Atlas (CGGA). METHODS: This study included 726 adults (age ≥ 18) with histologically proven anaplastic glioma or glioblastoma multiforme (GBM). The overall and progression-free survival was determined in young (age < 50) and older groups (age ≥ 50). RESULTS: The study included an older group (OP) of 264 patients and a younger group (YP) of 462patients. In the OP group with GBM and anaplastic glioma, patients treated with RT combined with temozolomide (TMZ) manifested significantly longer OS and PFS compared with patients assigned to RT alone (P < 0.05). In contrast, the YP group diagnosed with anaplastic glioma failed to show any survival advantage with RT plus TMZ compared with RT alone. CONCLUSIONS: We observed no survival benefit in young adults (age < 50) with anaplastic glioma when treated with TMZ combined with RT. Our findings warrant further investigation of younger patients diagnosed with anaplastic glioma treated with radiotherapy plus TMZ chemotherapy.